Nano-functionalized long-period fiber grating probe for disease-specific protein detection. Issue 3 (5th January 2018) - Tyagi, Deependra; Mishra, Satyendra Kumar; Zou, Bing; Lin, Congcong; Hao, Ting; Zhang, Ge; Lu, Aiping; Chiang, Kin Seng; Yang, Zhijun
Abstract : Label-free nano-functionalized LPFG based real-time, reusable sensor for sensitive detection of disease-specific proteins. Abstract : Optical biosensors have great significance for rapid and sensitive detection and monitoring of biomolecular interactions. Here, recent advancement in the nano-functionalized long-period fiber grating (LPFG) is used to develop a cost-effective approach for label-free and real-time detection of the carbonic anhydrase-IX (CA9) monoclonal antibody, a diagnostic biomarker in hypoxia condition cultured carcinoma cells.